Influence of family and child demographic characteristics on the incidence of stunting - Balgis, Balgis; Putri, Anak Agung Alit Kirti Estuti Narendra; Primaningtyas, Widana; Paramesti, Khansa Firyallely (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Stunting cases in Surakarta ranked fourth lowest in Central Java. However, the stunting target in Surakarta is zero. Objective: This study aimed to analyze the influence of maternal and child demographic factors on the incidence of stunting at the Gilingan Surakarta Community Health Center. Methods: This research method used analytical observations with a case-control research design. The research subjects were obtained using a simple random sampling method consisting of 38 stunted toddlers and 38 non-stunted toddlers aged 24-59 months at Gilingan Surakarta Community Health Center. Data collection was done by distributing questionnaires to respondents. The statistical test used for bivariate analysis is the chi-square, and multivariate analysis uses multiple logistic regression. Results: Bivariate analysis showed that maternal occupation (p=0.047) and family income (p=0.002) influenced the incidence of stunting. Multivariate analysis then found that maternal occupation and family income were associated with the incidence of stunting (p=0.005). Conclusion: The conclusion in this study was that mothers' occupation and family income significantly influence the incidence of stunting. Therefore, there is a need for assistance in the form of additional food for toddlers from underprivileged families to meet their nutritional needs so that stunting can be prevented.